The Effect of Problem Based Learning Model and Learning Styles on Motivation and Learning Outcomes in Acid-Base of Grade XI Students at SMA Negeri 18 Makassar - Siti Zurfiani Devi Rahman; Sudding; Sugiarti (Postgraduate, University of Mataram, 2026)
This study is a quasi-experimental research aimed to determine the effect of problem based learning model and learning styles on motivation and learning outcomes in acid-base of grade students XI at SMA Negeri 18 Makassar. The research design used is a factorial design 2×3. The research sample consisted of 60 students of grade XI who were divided into experimental groups and control groups. The sampling technique was carried out by random sampling. The data obtained were analyzed using descriptive and inferential statistics. The results of the study show that the problem based learning model has a significant effect on learning motivation and learning outcomes. Learning styles also has a significant effect on learning motivation and learning outcomes. In addition, the problem based learning model and learning style simultaneously had a significant effect on both bound variables. This shows that there is the effect of problem based learning and learning styles on motivation and learning outcomes in acid-base of grade XI students at SMA Negeri 18 Makassar.